Preoperative sequential chemotherapy and hypofractionated radiotherapy combined with comprehensive surgical resection for high-risk soft tissue sarcomas: a retrospective study - Qu, Guoxin; Tian, Zhichao; Wang, Jiaqiang; Yang, Chengliang; Niu, Xiaohui; Yao, Weitao (Frontiers in Oncology, 2024)
Introduction The management of soft tissue sarcomas presents considerable therapeutic challenges. This study was designed to assess the efficacy of neoadjuvant sequential chemotherapy and hypofractionated radiotherapy in conjunction with extensive surgical resection for the treatment of high-risk soft tissue sarcomas. Materials and methods We performed a retrospective review of 31 high-risk soft tissue sarcoma patients treated at our institution from June 2021 to June 2023. The cohort consisted of 21 males and 10 females with a mean age of 55.7 years and included both initial and recurrent disease presentations. Our treatment regimen comprised two to three cycles of neoadjuvant chemotherapy coupled with hypofractionated radiotherapy, delivered at 5 Gy per fraction to a total dose of 25–35 Gy across 5–7 days, prior to surgical resection aimed at achieving wide margins. Data collection was systematic, covering surgical outcomes, chemoradiotherapy-related complications, and prognostic factors. Results All patients completed the prescribed course of neoadjuvant chemoradiotherapy. 29% patients experienced grade 3+ chemotherapy toxicity, necessitating a reduction or interruption in their chemotherapy regimen. Limb preservation was accomplished in 30 patients finally. Response evaluation using RECIST 1.1 criteria post-neoadjuvant therapy revealed 9.7% with PD, 58.1% with SD, 29% with a PR, and 3.2% with a CR, culminating in an ORR of 32.2%. Postoperative complications included superficial wound infections in four patients and deep incisional infections in another four. 6 patients had developed metastasis, and 3 patients were still alive. Two experienced local recurrence. One-year DFS was 79.3%, with a one-year OS rate of 89.6%. Conclusion Neoadjuvant sequential chemotherapy and hypofractionated radiotherapy followed by extensive surgical resection represents an effective treatment paradigm for high-risk soft tissue sarcomas. This multimodal approach not only facilitates tumor reduction but also significantly reduces the risks of local recurrence and distant metastasis.